O Livro Didático de Língua Estrangeira: Atividades de compreensão e habilidades no processamento de textos na leitura - Juliana Esteves Arantes (2008)
The abilities involved in the process of reading in a foreign language (FL) should be developed in the activities of the English textbooks. The reading abilities considered as the theoretical framework in this study are those stated by the State of Minas Gerais official document which presents a pedagogical proposal for the teaching of English as a foreign language, PCSEE-MG (DIAS, 2005b). This document contains a common syllabus (CBC) that systematizes the necessary abilities to develop competence in English as a foreign language (EFL) and can serve as a parameter for the teaching of English. The present study aims at analyzing an English Textbook Collection for the second cycle of the Elementary School with focus on its written comprehension activities. This analysis is referred to the current theoretical principles for the teaching of reading in a foreign language (CELCEMURCIA & OLSHTAIN, 2000; CARREL & EISTERHOLD, 1988; DIAS, 2005b; GRABE & STOLLER, 2001, 2002; RAMOS, 2004) and is also supported by the recent research on textbook evaluation (ANSARY & BABAII, 2002; BYRD, 2001; EDMUNDSON, 2004; GRIGOLLETO, 2002; RACILAN, 2005, among others). Our study intends to verify if the written activities proposed in the textbooks are aimed to develop those referred specific reading abilities. The research methodology underlying this paper was based on qualitative principles and consists of a focused description (LARSEN-FREEMAN & LONG, 1991) as our interest resides specifically on the reading activities of the analyzed textbooks. The procedures of analyses used were the classification of the written comprehension activities according to the CBC stated reading abilities. The results were further displayed in tables and graphics to convey better visualization. Our findings confirmed the initial hypothesis of failure in the intent of developing reading fluency by the textbooks as they prioritarily emphasize the abilities of location of explicit information in the text, integration of verbal and non-verbal information, and to a lesser extent, inference of meaning based on the context and previous knowledge. Besides neglecting most of the necessary abilities involved in the process of reading in a FL, the activities analyzed also did not consider the concepts of textual genre that underlie the contemporary tendency in the teaching of reading in a FL. Reflection on this research data may lead to better comprehension of the processes underlying the current failure of schools in developing proficient readers, as well as may help improving the implementation and production of FL effective teaching materials.